Evaluation of charging and discharging performances of the rechargeable aluminium-air battery - Khoo, Wen Loong (2022)
Batteries are essential energy storage system widely utilized in our daily lives. Batteries provide power to the portable devices in our daily lives including car keys, laptops, smartphones, and vehicles. There are many types of batteries, the examples of these batteries include lithium-ion battery, alkaline battery, and metal-air battery. Recently, since the commercial lithium-ion battery is approaching its performance limit, the development of electric vehicles has encouraged the research on metal-air batteries, including the aluminium-air battery. High theoretical energy density of aluminium-air battery and the lightweight, wide availability at low cost, and safety of aluminium has further motivated the research in aluminium-air battery. In this project, a rechargeable aluminium-air battery was designed and developed using economic materials such as carbons, acrylics, and kitchen aluminium foil. This project consists of several findings. First of all, the mesh type current collector with greater number of openings per meter square provides better battery performance. Next, the optimum loadings of reduced graphene oxide are 15 mg in total of 330 mg of catalyst mixture (approximately 4.5% mass ratio). For separators, non-woven membrane (glass fiber separator) allows better battery performance than cellulose membrane (filter paper separator). With the combinations of the components that provides the best results, the developed aluminium-air battery was able to exhibits the energy density of 297 mWh/g. Finally, addition of additives into the aqueous electrolyte was able to inhibits the formation for aluminium hydroxide and parasitic hydrogen evolution reaction. However, the suppression of the impurities and the hydrogen evolution does not provide the battery with long-term rechargeability.